SOCIALIZING MULTICULTURAL EDUCATION PRACTICES FOR ELEMENTARY SCHOOL TEACHERS IN THE PROVINCE OF JAKARTA IN INDONESIA - Arifin Maksum; Maratun Nafiah; Sutrisno Sutrisno; Arita Marini; Desy Safitri; Sujarwo Sujarwo; Nurzengky Ibrahim (JURNAL PENGABDIAN MANDIRI, 2022)
Location of this international collaboration of community service is in the Province of Jakarta in Indonesia. The target of this community service is elementary school teachers in the Province of Jakarta in Indonesia. The problem with the target audiences is that the competences in applying multicultural education practices of elementary school teachers in the Province of Jakarta in Indonesia has not been managed properly and their interests in implementing it are still low. In addition to this, the socialization of applying multicultural education practices for elementary school teachers in the Province of Jakarta in Indonesia has not been done before. In order to develop the competences of multicultural education practices of elementary school teachers to create equal educational opportunities for all students by changing the total class environment so that it will reflect the diverse cultures and groups within the classrooms at elementary schools in the province of Jakarta in Indonesia, the solution is socializing multicultural education practices.